1996
DOI: 10.1295/polymj.28.24
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Solid State 13C NMR Spectroscopy of Polypropylene with Very High Syndiospecificity

Abstract: ABSTRACT:The high resolution solid state 13 C NMR spectra were observed for highly syndiotactic polypropylene samples with three kinds of crystalline forms, forms I, II, and III. The forms I and II are the most stable helical conformation, (-TTGG-), and all trans planar zigzag conformation, respectively. The sample with the third new crystalline form, form Ill, was prepared by soaking the sample with form II in toluene at room temperature for two days. The conformation was proposed to be (-T 6 G2 T2 G2-). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…The spectra of all the sPP fibers show peaks at 19, 27, and 48 ppm, along with a shoulder at 21 ppm on the methyl peak. Such a spectrum with a single distinct methylene peak (48 ppm) arises from a mostly (TTTT) conformation 18, 19, 21, 22, 37. The methylene carbons do not receive any γ‐ gauche effect in the trans planar conformation and exhibit only a single peak.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectra of all the sPP fibers show peaks at 19, 27, and 48 ppm, along with a shoulder at 21 ppm on the methyl peak. Such a spectrum with a single distinct methylene peak (48 ppm) arises from a mostly (TTTT) conformation 18, 19, 21, 22, 37. The methylene carbons do not receive any γ‐ gauche effect in the trans planar conformation and exhibit only a single peak.…”
Section: Resultsmentioning
confidence: 99%
“…For example, although syndiotactic polypropylene (sPP) was first synthesized in 1960s by Natta et al,1 significant interest in the polymer did not result until the work of Ewen et al in 1988,2 which facilitated the production of highly syndiospecific polypropylene. Renewed research interest in sPP has produced several reports3–23 on processing, structure, and properties of this polymer, and also on comparisons with its isotactic analog (iPP), a polymer that has been in large‐scale production for approximately four decades. Among the various aspects of sPP, the most significant with regard to its applications pertains to its crystallization characteristics.…”
Section: Introduction and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown [38,39] by high-resolution solid-state 13 C NMR spectroscopy that annealing of the trans-planar form III at about 50 8C it results in a transformation to the helical conformation. Bonnet et al [31] mention that when a highly strained sample of sPP in trans-planar form III is annealed, a transformation of the trans-planar chains into the helical chain conformation takes place above 80 8C.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of investigations on the molecular chain conformation and molecular packing in crystals have also been reported for sPP. As for the polymorphs, four crystalline forms are known: the planar zigzag, t 2 g 2 t 6 g 2 , and two forms with the t 2 g 2 conformation. Of these, the crystals with the planar zigzag conformation have been believed to be formed only by cold drawing after quenching from the melt into an ice−water mixture. Very recently, we have found that the crystallization of the planar zigzag form is spontaneously induced at 0 °C without any mechanical stress, although the growth rate is very slow. In this communication, we report briefly the first results to confirm such spontaneous crystallization of the form at 0 °C, which have been obtained by CP/MAS 13 C NMR and wide-angle X-ray scattering methods.…”
mentioning
confidence: 99%